Status Gizi Dan Karakteristik Orang Tua Pada Siswa Dengan Perawakan Pendek di SD Negri 065853 Medan - Ika Nopa (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2019)
The Sustainable Development Goals (SDGs) target in 2030 to end all forms of malnutrition. In Indonesia, nutrition problems are still a public health problem. In school-age children it is necessary to fulfill nutrition not only to ensure the growth and development of children but also to optimize their physical, mental and social aspects so that they are able to become productive generations. Nutritional imbalance can reduce the quality of human resources which will ultimately hinder national development. This study aims to assess nutritional status and characteristics of parents in short stature students. This study used a cross sectional study design. The sample was 77 elementary school students 065853 Medan. The number was determined using proportion sample formula for one precision population sample and using proportional stratified random sampling technique in sample selection.Data on nutritional status and parental characteristics were obtained through anthropometric measurements and questionnaires. The collected data was then analyzed univariately. The results of the study found the highest nutritional status in the underweight. For distribution in short stature children found the highest nutritional status in the underweight category. Distribution of short stature children according to the characteristics of parents found the highest maternal education in the middle category, the highest maternal knowledge in the good category and the highest income of parents in the low category.